The Effect of Using Google Maps on Spatial Literacy Skills in Disaster Mitigation Materials in Geography Classes: An Experimental Study on Grade 11 Students at Jeruklegi State Senior High School 1 - Agus Supriyanto; Anang Widhi Nirwansyah; Beny Wijarnako K (Interdisciplinary Social Studies, 2026)
This research is motivated by the low level of spatial literacy of students and the limited use of technology-based interactive learning media in geography learning, especially in disaster mitigation materials. The purpose of this study is to analyze the effect of the use of Google Maps on students' spatial literacy skills in disaster mitigation materials in geography learning at State of Senior High School 1 Jeruklegi. The research employed a quantitative approach with a quasi-experimental design using a pretest-posttest control group design. The sample consisted of two classes: an experimental class that received inquiry-based learning assisted by Google Maps, and a control class that received conventional learning without the use of the media. Data were collected through spatial literacy tests and student response questionnaires. The results indicate that there is a difference in the improvement of spatial literacy skills between the experimental and control classes. The use of Google Maps has a significant effect on enhancing students’ spatial literacy, particularly in terms of understanding spatial concepts, using spatial representation tools, and reasoning and analyzing spatial relationships. Therefore, the use of geospatial technology-based learning media such as Google Maps can serve as an innovative alternative to improve the quality of geography learning, especially in disaster mitigation materials.